Expert System for Diagnosis of Pepper Plant Diseases Using Certainty Factor and Naïve Bayes Methods - Karmila; Eny Maria; Annafi' Franz (Politeknik Pertanian Negeri Samarinda, 2021)
Development expert system for diagnosis of pepper plant diseases using certainty factor and naïve bayes methods. Pepper is one type of plant that has long been traded on the European market. So that increasing the quality and quantity of pepper production is the main demand. However, diseases in pepper plants are also familiar to be found so that they can be detrimental to farmers and besides that, agricultural workers who are experts in the field of pepper plant diseases are still limited. Therefore, to overcome this problem, an expert system application is designed where this system can provide information about diseases that attack pepper plants, then provide suggestions or solutions to deal with these diseases. The purpose of this research is to build and design an expert system that is useful for determining pepper plant diseases and to apply certainty factor and nave Bayes methods in providing answers to the results of the consultation. The results of this study are expected to make it easier for users, especially farmers or farm workers in overcoming diseases in pepper plants.